Enhancing Financial, Legal, and Risk Management for MSMEs in Brunei Darussalam: Strategies for Sustainable Growth - Saputra Hasibuan, Edi; Suraji, Robertus; Ikhsan, Arfan; Sastrodiharjo, Istianingsih (International Journal of Advanced Multidisciplinary, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Brunei Darussalam's economy, playing a significant role in employment absorption and contributing notably to the Gross Domestic Product (GDP). However, MSMEs in Brunei often face challenges in financial management, legal compliance, and identifying as well as managing operational risks. This Community Service Program aims to equip MSMEs in Brunei with practical skills related to financial management, legal compliance, and risk mitigation tailored to their operational context. Based on a literature review and the implementation results, this paper outlines comprehensive strategies to assist MSMEs in addressing these challenges and fostering business sustainability. The findings indicate that this educational intervention significantly enhances the awareness and capabilities of MSMEs in Brunei in managing financial and legal challenges, while also preparing them for audits by regulators.